Does longer leukocyte telomere length and higher physical fitness protect master athletes from consequences of coronavirus (SARS-CoV-2) infection? - Simões, H. G.; Santos Rosa, T.; Sousa, C. V.; da Silva Aguiar, S.; Motta-Santos, D.; Degens, H.; Korhonen, M. T.; Grubert Campbell, C. S. (Frontiers in Sports and Active Living, 2020)
The higher physical fitness, better health, lower inflammation, better redox balance, and the longer leukocyte telomere length of master athletes indicates they are not only biologically younger than their calendar age suggests, but are also expected to have a better ability to successfully face a COVID-19 disease than their frail sedentary age-matched peers.